A High‐Energy‐Density Asymmetric Microsupercapacitor for Integrated Energy Systems. (25th March 2015) - Wang, Fengmei; Zhan, Xueying; Cheng, Zhongzhou; Wang, Qisheng; Wang, Zhenxing; Wang, Feng; Xu, Kai; Huang, Yun; Safdar, Muhammad; He, Jun
<x xml:space="preserve">Abstract</x> An asymmetric micrometer‐sized pseudosupercapacitor is fabricated by growing V2O5 honeycomb nanostructures onto micro‐carbon fibers, which serve as the positive electrode. WO3/PPy core/shell nanoarrays on micro‐carbon fibers serve as the negative electrode. The all‐solid‐state pseudosupercapacitor shows a volumetric specific capacitance as high as ≈56 F cm−3 and a volumetric energy density of ≈31.1 mWh cm−3 while maintaining a high power density. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>